Factors Influencing the Microstructure and Corrosion Resistance of Austenitic and Duplex Stainless Steel Castings - Pearce , John T. H.; Bhandhubanyong, Paritud (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2020)
The demand for Austenitic and Duplex Stainless Steel Castings has increased with investment in the petrochemical industry, transportation infrastructure and electric vehicle production in Thailand. To achieve high quality casting of these two grades, alloying elements melt quality, pre- and post—treatment of castings play an important role in quality level determination. These important factors are discussed along with guidelines for good manufacturing practices to achieve the required microstructures and high quality castings from the domestic foundry sector in Thailand.